Quality Control Strategy for CRISPR-Cas9-Based Gene Editing Complicated by a Pseudogene - Hanss, Zoé; Boussaad, Ibrahim; Jarazo, Javier; Schwamborn, Jens C.; Krüger, Rejko (Frontiers in Genetics, 2020)
CRISPR-Cas9 mediated gene editing in induced pluripotent stem cells became an efficient tool to investigate biological mechanisms underlying genetic-driven diseases while accounting for the respective genetic background. This technique relies on the targeting of a specific nucleotide sequence present in the gene of interest. Therefore, the gene editing of some genes can be complicated by non-coding pseudogenes presenting a high homology of sequence with their respective genes. Among them, GBA is raising special interest because of its implication as the most common genetic risk factor for Parkinson’s disease. In this study, we present an easy-to-use CRISPR-Cas9 gene editing strategy allowing for specific editing of point mutations in a gene without genetic alteration of its pseudogene exemplified by the correction or insertion of the common N370S mutation in GBA. A quality control strategy by combined fluorescence and PCR-based screening allows the early identification of correctly edited clones with unambiguous identification of the status of its pseudogene, GBAP1. Successful gene editing was confirmed by functional validation. Our work presents the first CRISPR-Cas9 based editing of a point mutation in GBA and paves the way for technically demanding gene engineering due to the presence of pseudogenes.